The determinants of balance of trade in China / Nurerina Zahirah Zainalabidin Sebli - Zainalabidin Sebli, Nurerina Zahirah (Faculty of Business and Management, 2018)
Using yearly data over the period 1976 - 2016, this study examine the China’s Balance of Trade by using several macroeconomic variables which are real exchange rate (REER), consumer price index (CPI), domestic income (DOMINC), foreign direct investment (FDI) and inflation rate (INF). The study introduces about the nature of balance of trade and what affects the balance of trade. The study also uses time series with observation of 41. The objective of the study is also to examine the relationship between the balance of trade and the independent variables which are real exchange rate (REER), consumer price index (CPI), domestic income (DOMINC), foreign direct investment (FDI) and inflation rate (INF). The study will examine the relationship whether it will give impact to the independent variable, significantly or insignificantly. Empirical results shows that real exchange rate is negatively insignificant, consumer price index is negatively insignificant, domestic income as positively significant, foreign direct investment is negatively insignificant and inflation rate to be positively significant.